Output control device for power distribution line fault indicator detection - HOU YUTIAN; LIU LAN; LIANG YING; TANG KEXIN; LI BAIKUI (2014)
The invention provides an output control device for power distribution line fault indicator detection. The device comprises a DSP module, a DAC module, a power amplifier and an optical fiber communication module. The DSP module receives parameters and commands output by an upper computer, and controls the DAC module to output a simulated alternating voltage signal and an alternating current signal. The power amplifier receives the alternating signals output by the DAC module, amplifies the received alternating signals and transmits the amplified alternating signals to a boosting transformer and a boosting coil. The optical fiber communication module receives an optical fiber signal from a data collection device and analyzes motion information and reset state information of a fault indicator from the optical fiber signal, and the motion information and the reset state information of the fault indicator are uploaded to the upper computer through the DSP module. According to the output control device, the output